A cross-sectional survey of cardiovascular health and lifestyle habits of hospital staff in the UK: Do we look after ourselves?. (March 2018) - Mittal, Tarun K; Cleghorn, Christine L; Cade, Janet E; Barr, Suzanne; Grove, Tim; Bassett, Paul; Wood, David A; Kotseva, Kornelia
Background: A high prevalence of stress-related disorders is well known among healthcare professionals. We set out to assess the prevalence of cardiovascular risk factors and compliance with national dietary and physical activity recommendations in NHS staff in the UK with comparison between clinical and non-clinical staff, and national surveys. Design: A multi-centre cross-sectional study. Methods: A web-based questionnaire was developed to include anonymised data on demographics, job role, cardiovascular risk factors and diseases, dietary habits, physical activity and barriers towards healthy lifestyle. This was distributed to staff in four NHS hospitals via emails. Results: A total of 1158 staff completed the survey (response rate 13%) with equal distribution between the clinical and non-clinical groups. Most staff were aged 26–60 years and 79% were women. Half of the staff were either overweight or obese (51%) with no difference between the groups ( P = 0.176), but there was a lower prevalence of cardiovascular risk factors compared to the general population. The survey revealed a low compliance (17%) with the recommended intake of five-a-day portions of fruit and vegetables, and that of moderate or vigorous physical activity (56%), with no difference between the clinical and non-clinical staff ( P = 0.6). However, more clinical staff were exceeding the alcohol recommendations ( P = 0.02). Lack of fitness facilities and managerial support, coupled with long working hours, were the main reported barriers to a healthy lifestyle. Conclusions: In this survey of UK NHS staff, half were found to be overweight or obese with a lower prevalence of cardiovascular risk factors compared to the general population. There was a low compliance with the five-a-day fruit and vegetables recommendation and physical activity guidelines, with no difference between the clinical and non-clinical staff.